2012
DOI: 10.3892/ijo.2012.1446
|View full text |Cite
|
Sign up to set email alerts
|

PAX2 is an antiapoptotic molecule with deregulated expression in medulloblastoma

Abstract: Abstract. PAX2 is a paired box transcription factor possessing a fundamental role in the embryogenesis of hindbrain and urinary tract. PAX genes are proto-oncogenes, PAX2 expression may contribute to the pathogenesis of renal cell carcinoma. Because of the expression of PAX2 in the developing hindbrain and its essential role in cerebellar development, it has been hypothesized that PAX2 may also be involved in medulloblastoma tumorigenesis. We investigated the expression pattern of PAX2 and various genes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Although structurally similar, each PAX gene imparts unique downstream effects and varies in its regulatory contributions to organogenesis. PAX1, for example regulates epithelial differentiation within and development of the thymus (Mansouri et al, 1999), whereas PAX2 has been shown to regulate the response of kidney mesenchyme to induction (Dressler, 1995), and is involved in embryogenesis of the hindbrain (Eccles, 1998) and epithelial differentiation within the urogenital tract (Burger et al, 2012). PAX3 has strong and preferential expression in neurodevelopment with the synthesis of PAX3 occurring in the dorsal neural tube (Chi and Epstein, 2002), and regulatory effects playing a critical role in both fate determination of neural crest cells and their differentiation into enteric and peripheral ganglia, Schwann cells and melanocytes (Nelms and Labosky, 2010).…”
Section: Pax Genesmentioning
confidence: 99%
“…Although structurally similar, each PAX gene imparts unique downstream effects and varies in its regulatory contributions to organogenesis. PAX1, for example regulates epithelial differentiation within and development of the thymus (Mansouri et al, 1999), whereas PAX2 has been shown to regulate the response of kidney mesenchyme to induction (Dressler, 1995), and is involved in embryogenesis of the hindbrain (Eccles, 1998) and epithelial differentiation within the urogenital tract (Burger et al, 2012). PAX3 has strong and preferential expression in neurodevelopment with the synthesis of PAX3 occurring in the dorsal neural tube (Chi and Epstein, 2002), and regulatory effects playing a critical role in both fate determination of neural crest cells and their differentiation into enteric and peripheral ganglia, Schwann cells and melanocytes (Nelms and Labosky, 2010).…”
Section: Pax Genesmentioning
confidence: 99%
“…Knockdown of PAX2 expression with a short hairpin RNA confirmed the role of PAX2 in the promotion of metastasis in ESCC cells, which supports the findings obtained by examining ESCC tissues that PAX2 expression is associated with pN and lymphatic invasion. The downstream target genes of PAX2 have gradually been identified, and GDNF has been reported to be a PAX2 target in medulloblastoma [36]. PAX2 can regulate metalloproteinase ADAM10 expression by driving melanoma metastasis [39].…”
Section: Discussionmentioning
confidence: 99%
“…PAX2 overexpression exhibits oncogenic properties, such as anti-apoptosis, proliferation promotion and drug resistance in multiple cancers [36,37]. The function of PAX2 in proliferation has proven to be controversial, depending on the genetic background of cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…PAX genes have been shown to act as either tumor promoters or suppressors and are implicated in the pathogenesis of several human cancers, including brain tumors. PAX2 has been found expressed in medulloblastoma cells and associated with a more aggressive phenotype [9] while PAX5 expression levels were correlated with increasing malignancy of astrocytomas [10]. On the contrary, PAX6 inhibited glioma cell proliferation and invasiveness and affected chemoresistance to temozolamide [11], [12].…”
Section: Introductionmentioning
confidence: 99%